2019
DOI: 10.1111/zsc.12373
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny and timing of evolution ofAnthomyzaand related genera (Diptera: Anthomyzidae)

Abstract: Phylogenetic hypotheses of the relationships of Diptera: Anthomyzidae (61 taxa) are discussed with special reference to the genera Fungomyza Roháček, 1999, Anthomyza Fallén, 1810, Epischnomyia Roháček, 2006 and Arganthomyza Roháček, 2009 based on the analysis of 7 combined mitochondrial + nuclear gene markers in comparison with results of the most recent cladistic analysis of morphological characters. The majority of revealed inter‐ and intrageneric relationships of these genera in both analyses were largely c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, based on analysis of morphological data, they recognized M. nigrimana (and its numerous undescribed Neotropical relatives) to be most closely related to species of Stiphrosoma, not to M. occipitalis. Subsequent phylogenetic hypotheses based on analyses of molecular data (Roháček & Tóthová 2014;Roháček et al 2019) have confirmed the above relationships. Currently, there are four named species affiliated with the genus Mumetopia, but only three of them belong, in fact, to the genus (in the restricted concept, see Roháček & Barber 2009), viz., M. occipitalis (widespread in North America), M. messor Roháček & Barber, 2009 (Ecuador) and M. taeniata Roháček & Barber, 2009 (Colombia).…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…Furthermore, based on analysis of morphological data, they recognized M. nigrimana (and its numerous undescribed Neotropical relatives) to be most closely related to species of Stiphrosoma, not to M. occipitalis. Subsequent phylogenetic hypotheses based on analyses of molecular data (Roháček & Tóthová 2014;Roháček et al 2019) have confirmed the above relationships. Currently, there are four named species affiliated with the genus Mumetopia, but only three of them belong, in fact, to the genus (in the restricted concept, see Roháček & Barber 2009), viz., M. occipitalis (widespread in North America), M. messor Roháček & Barber, 2009 (Ecuador) and M. taeniata Roháček & Barber, 2009 (Colombia).…”
Section: Introductionmentioning
confidence: 80%
“…Except for two additions (M. interfeles sp. nov. and Stiphrosoma stylatum Roháček & Barber, 2005), they are listed in full (with names, authors and source localities of analysed specimens) in Roháček et al (2019: table 1, most species) and Barber & Roháček (2020: table 1, species of Carexomyza Roháček, 2009). We used one specimen per species except for an unnamed species of the M. nigrimana group, of which we processed two specimens.…”
Section: Taxon Samplingmentioning
confidence: 99%
See 3 more Smart Citations